Miniaturised implantable circular polarized antenna with a high ARBW - Rajiv Kumar Nehra; Ajay Dureja; Rajkumar Singh Rathore; Tiansheng Yang; Lu Wang (PLoS ONE, 2025)
For biological applications, this communication uses an implanted antenna loaded with metamaterial and a sorting pin. The suggested antenna operates at 2.44 GHz in the ISM band. The first antenna’s resonant frequency is lowered from 2.53 GHz to 2.46 GHz by applying a sorting pin. This causes the antenna to become circularly polarized and have an ARBW of 580 MHz (2.15 GHz - 2.73 GHz). Strong CP behavior with an ARBW of 830 MHz from 2.01 GHz to 2.84 GHz in the ISM band is produced by incorporation of an H-shaped metamaterial on the antenna’s superstrate. Additionally, the reasonable value of the specific absorption rate improved from 960.5 to 952.1. Highlights of the suggested antenna include its miniature size (10.67 mm3), strong CP properties, the significant value of SAR 952.1 W/KG, and unslotted ground plane to detract from designing labyrinthine backscattering radiation. After building the recommended antenna, experiments are conducted using a skin-mimicking gel solution that approximates the electrical characteristics of human skin tissues at 2.44 GHz. In the ISM band, actual and simulated impedance bandwidths of 90 MHz and 110 MHz are acquired, respectively. Together with parametric analysis, simulation and measurement results are consistent.